Analisis Faktor Pengetahuan, Sikap dan Ketersediaan Sarana Prasarana terhadap Penerapan PHBS di Kost Eksklusif Mara Juara Depok - Santoso, Doni; Sulistiyorini, Desy; Sari, Agustina (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2024)
PHBS in the household setting is an effort to empower household members to be aware, willing and able to carry out PHBS to maintain and improve their health, prevent the risk of disease and protect themselves from the threat of disease and play an active role in the health movement in the community. The purpose of this research is to determine the relationship between knowledge, attitudes and availability of infrastructure and the implementation of PHBS at the Mara Juara Depok Exclusive Boarding House in 2023. This research uses a quantitative type of research with a descriptive analytical research design using a cross sectional approach and a sampling technique using total sampling with the number of sample of 36 respondents. The subjects of this research were residents of the Mara Juara Depok Exclusive Boarding House. Data analysis was carried out univariate and bivariate. Based on the results of statistical tests related to the availability of infrastructure, the p-value = 0.023 (p<0.05), while for the knowledge variable the p-value = 0.078 (p>0.05), the p-value = 0.346 (p>0.05). 0.05). It can be concluded that there is a variable relationship between the availability of infrastructure and the implementation of PHBS in the exclusive boarding house for the champions in Depok. It is recommended that boarding house managers provide explanations to boarding house residents regarding the use of existing infrastructure in the boarding house, so that the infrastructure provided can be used properly.